PEREMPUAN DAN KESEJAHTERAAN KELUARGA DALAM PERSPEKTIF EKONOMI ISLAM - Hernidar Hernidar; Putri Apria Ningsih; M. Maulana Hamzah (Jurnal Kajian dan Penalaran Ilmu Manajemen, 2023)
Nowadays, in the era of globalization, in the era of progress, there is increasing interaction and integration between countries in economic, political, social and cultural terms. Not only men can work or trade but also women, whether they are married or not. In this regard, this research aims to find out what are the causal factors that make women work as traders at the Friday market, Kotabaru Seberida Village, Indragiri Hilir Regency, Riau. Then what is the role of female traders in the Friday market as a wife and mother from an Islamic economic perspective? In this research the author used a qualitative approach. And the data sources used are primary and secondary data sources. Meanwhile, the data collection techniques used are observation, interviews and documentation. Based on research results, there are 2 factors that cause women to work as traders in the Friday market, namely internal and external factors. Internal factors, self-will, meeting family economic needs, educational factors. External factors, large number of family dependents, family encouragement, cost of living. Meanwhile, the role of female traders as a wife and mother in an Islamic economic perspective. Not forgetting his role, being able to carry out his role even though not optimally, but still being able to maintain the integrity of his family and being able to educate his children well, even indirectly and at all times with his children, but always providing good exemplary examples in words and deeds, always reminding - positive things so as not to be influenced by negative associations, whereas in the Islamic economic perspective the role of female traders as a wife and mother, there is no prohibition for a woman to work as long as in her work she pays attention to ethical values, good morals, does not forget her physical and psychological nature, is able to dividing time between family demands and work demands, women are allowed to work.